The Role of Board of Commissioners in Islamic Social Reporting - Luluk Muhimatul Ifada; Chrisna Suhendi; Rustam Hanafi (Jurnal Economia, 2021)
Abstract: This research aims to investigate how the board of commissioners plays a role in influencing Islamic social reporting. The object of this study was the disclosure of Islamic social reporting in sharia banking in Indonesia, through secondary data. Data were analyzed using multiple linear regression analysis. The findings showed the role of the board of commissioners in influencing the extent of Islamic social reporting disclosure more likely through the size of the board of commissioners, not through an independent board of commissioners or the number of board meetings. Researchers found that challenge of a great opportunity for the board of commissioners to contribute to social responsibility of companies in accordance with the provisions of Islam.  Keywords: Islamic social reporting, board of commissioners, sharia banks Peran Dewan Komisaris dalam Islamic Social ReportingAbstrak: Penelitian ini bertujuan untuk mengetahui peran dewan komisaris dalam mempengaruhi Islamic social reporting. Objek penelitian ini adalah pengungkapan Islamic social reporting pada perbankan syariah di Indonesia, melalui data sekunder. Analisis data menggunakan analisis regresi linier berganda. Temuan menunjukkan bahwa peran dewan komisaris dalam mempengaruhi pengungkapan Islamic social reporting cenderung melalui ukuran dewan komisaris, bukan melalui dewan komisaris independen atau jumlah rapat dewan. Peneliti menemukan bahwa terdapat tantangan yang menjadi peluang besar bagi dewan komisaris untuk berkontribusi pada tanggung jawab sosial perusahaan sesuai dengan ketentuan Islam.Kata kunci: Islamic social reporting, board of commissioners, bank syariah